Variation of Growth Dynamics and Resource Allocation Patterns of Dictamnus albus: Variation of Growth Dynamics and Resource Allocation Patterns of Dictamnus albus - Nissar, Saduf (International Journal of Pharmaceutical & Biological Archive, 2019)
Dictamnus albus is a medicinally important plant distributed throughout South and central Europe, temperate Asia, and Himalayas. The present study was devised for the 1st time to understand the variation in growth characteristics and changes in allocation patterns in relation to altitude and habitats of Kashmir Himalaya. The present investigation revealed extensive variability in morphological parameters both within and across the individuals of different populations. Our findings clearly displayed significant divergence among sites which reveal a definite impact of altitude and habitat on morphological and reproductive features of the species under study. Our results are very useful to introduce the species into cultivation and developing strategies for conservation.